Perinatal outcomes and cost-effectivity of the assisted reproduction pregnancies with advanced age: A retrospective analysis. (19th May 2017) - Yilmaz, Nafiye; Kara, Mustafa; Coskun, Bugra; Kaba, Metin; Erkilinc, Selçuk; Yenicesu, Okan; Erkaya, Salim
Abstract: We demonstrated the IVF-ICSI results, perinatal outcomes and cost-effectivity of the patients with advanced age at a tertiary centre. A total of 456 patients categorised into two groups according to age: group 1 ( n  = 158) (≥39years) and group 2 ( n  = 298) (<39years) were analysed retrospectively. In addition, subgroup analysis was performed according to the 40 years cut-off. Clinical pregnancy rate was significantly different between the groups ( p < .001). Preterm delivery (< 37 gestational week) and low birth weight (< 2500 g) were significantly higher in advanced aged women than youngsters ( p < .001). Mean expense per cycle for hormonal stimulation of IVF-ICSI was 1058.9 and 723.5 USD in groups 1 and 2, respectively ( p < .001). Mean expense per pregnancy was 9294.7 and 1874.8 USD in groups 1 and 2, respectively ( p < .001). Our study showed that perinatal outcomes and cost-effectivity might be adversely affected with increasing age.